Somatic embryogenesis receptor-like kinase 5 in the ecotype Landsberg erecta of Arabidopsis is a functional RD LRR-RLK in regulating brassinosteroid signaling and cell death control - Wu, Wangze; Wu, Yujun; Gao, Yang; Li, Meizhen; Yin, Hongju; Lv, Minghui; Zhao, Jianxin; Li, Jia; He, Kai (Frontiers in Plant Science, 2015)
In plants, LRR-RLKs play central roles in regulating perception of extracellular signals and initiation of cellular responses under various environmental challenges. Arabidopsis SERK genes, including SERK1 to SERK5, constitute a LRR-RLK sub-family. SERK1, SERK2, SERK3/BAK1, and SERK4/BKK1 have been well characterized to function as crucial regulators in multiple physiological processes such as brassinosteroid signaling, cell death control, pathogenesis, and pollen development. Despite extremely high sequence identity with BKK1, SERK5 is reported to have no functional overlapping with BKK1, which is previously identified to regulate BR and cell death control pathways, probably due to a natural mutation in a highly conserved RD motif in the kinase domain of SERK5 in Col-0 ecotype. Through a gene sequencing analysis in several Arabidopsis accessions, we are able to identify SERK5 in Landsberg erecta (Ler) genome encoding a LRR-RLK with an intact RD motif. Overexpression of SERK5-Ler partially suppresses the BR defective phenotypes of bri1-5 and bak1-3 bkk1-1, indicating SERK5-Ler functions as a positive regulator in BR signaling. Furthermore, the interaction between SERK5-Ler and BRI1 is confirmed by yeast two-hybrid and BiFC assays, and the genetic result showing that elevated expression of a kinase-dead form of SERK5-Ler causes a dominant-negative phenotype in bri1-5. In addition, overexpression of SERK5-Ler is capable of delaying, not completely suppressing, the cell death phenotype of bak1-3 bkk1-1. In this study, we first reveal that SERK5-Ler is a biologically functional component in mediating multiple signaling pathways.